2008
DOI: 10.1007/s00044-008-9130-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of 4-benzoyl-1-(4-carboxy-phenyl)-5-phenyl-1H-pyrazole-3-carboxylic acid and derivatives

Abstract: A new 1H-pyrazole-3-carboxylic acid 2, along with hydrazono-pyridazinone 3, a by-product, and its derivatives 4-7 were synthesized and the structures confirmed by infrared (IR) and 1 H and 13 C nuclear magnetic resonance (NMR) data. These new compounds were evaluated for their antibacterial activities against Gram-positive and Gram-negative bacteria using the tube dilution method. The minimal inhibitory concentrations (MICs) experiments revealed that most compounds exerted inhibitor effects against Klebsiella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Pyrazole and its derivatives are an important class of compounds and attracted widespread attention because of their pharmacological properties, been reported to have a large spectrum of biological effects (antidepressant, anxiolytic, antiallergenic, antihypertensive, hypoglycemic, insecticidal, and fungicidal), currently, certain pyrazole derivatives being extensively employed as pharmaceuticals. The speciality literature mentions several pyrazole compounds with analgesic (Amir and Kumar, 2005), anti-inflammatory (Zelenin et al, 1999), and antimicrobial activities (Akihiko et al, 2005;Bildirici et al, 2008;Goda et al, 2003;Korgaokar et al, 1996, Nauduri and Reddy, 1998, Susant et al, 2007Udupi et al, 1998). Some pyrazole derivatives have the advantage of possesing all these three actions (Adnan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole and its derivatives are an important class of compounds and attracted widespread attention because of their pharmacological properties, been reported to have a large spectrum of biological effects (antidepressant, anxiolytic, antiallergenic, antihypertensive, hypoglycemic, insecticidal, and fungicidal), currently, certain pyrazole derivatives being extensively employed as pharmaceuticals. The speciality literature mentions several pyrazole compounds with analgesic (Amir and Kumar, 2005), anti-inflammatory (Zelenin et al, 1999), and antimicrobial activities (Akihiko et al, 2005;Bildirici et al, 2008;Goda et al, 2003;Korgaokar et al, 1996, Nauduri and Reddy, 1998, Susant et al, 2007Udupi et al, 1998). Some pyrazole derivatives have the advantage of possesing all these three actions (Adnan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are several review articles by Shawali et al covering their reactions and applications [1][2][3][4][5][6][7][8][9]. Also, literature reports indicate that many pyrazole derivatives found use in various pharmaceutical, agrochemical and many other applications [10][11][12][13][14][15][16][17]. In the light of these facts and in conjunction with our ongoing studies of the chemistry of hydrazonoyl halides, it was thought interesting to study the 1,3-dipolar cycloaddition of the nitrilimines derived from hydrazonoyl halides to the enamino ester, namely (E)-ethyl 3-(dipropylamino)-acrylate 1, which has not been reported hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…They are important substances and have gained widespread attention due to their biological activities. Several studies have revealed that pyrazoles have important properties: antimicrobial [2,3] analgesic [4,5], antiviral [6,7], antitumor [8,9], anti-inflammatory [10,11], cytotoxic [12], antihistaminic [13], pesticidal [14], antifungal [15,16], anticonvulsant [17] and antidepressant [18].…”
mentioning
confidence: 99%
“…The antibacterial activity of 4-benzoyl-1-(4-carboxyphenyl)-5-phenyl-1H-pyrazole-3-carboxylic acid (P3CA) affects Grampositive and Gram-negative bacteria [3]. The biodistribution of P3CA has not been investigated.…”
mentioning
confidence: 99%